Cytisine Exerts an Anti-Epileptic Effect via α7nAChRs in a Rat Model of Temporal Lobe Epilepsy - Zheng, Jing-jun; Zhang, Teng-yue; Liu, Hong-tao; Huang, Ze-xin; Teng, Jing-mei; Deng, Jing-xian; Zhong, Jia-gui; Qian, Xu; Sheng, Xin-wen; Ding, Ji-qiang; He, Shu-qiao; Zhao, Xin; et al. (Frontiers in Pharmacology, 2021)
Background and Purpose: Temporal lobe epilepsy (TLE) is a common chronic neurological disease that is often invulnerable to anti-epileptic drugs. Increasing data have demonstrated that acetylcholine (ACh) and cholinergic neurotransmission are involved in the pathophysiology of epilepsy. Cytisine, a full agonist of α7 nicotinic acetylcholine receptors (α7nAChRs) and a partial agonist of α4β2nAChRs, has been widely applied for smoking cessation and has shown neuroprotection in neurological diseases. However, whether cytisine plays a role in treating TLE has not yet been determined. Experimental Approach: In this study, cytisine was injected intraperitoneally into a pilocarpine-induced epileptic rats for three weeks. Alpha-bungarotoxin (α-bgt), a specific α7nAChR antagonist, was used to evaluate the mechanism of action of cytisine. Rats were assayed for the occurrence of seizures and cognitive function by video surveillance and Morris water maze. Hippocampal injuries and synaptic structure were assessed by Nissl staining and Golgi staining. Furthermore, levels of glutamate, γ-aminobutyric acid (GABA), ACh, and α7nAChRs were measured. Results: Cytisine significantly reduced seizures and hippocampal damage while improving cognition and inhibiting synaptic remodeling in TLE rats. Additionally, cytisine decreased glutamate levels without altering GABA levels, and increased ACh levels and α7nAChR expression in the hippocampi of TLE rats. α-bgt antagonized the above-mentioned effects of cytisine treatment. Conclusion and Implications: Taken together, these findings indicate that cytisine exerted an anti-epileptic and neuroprotective effect in TLE rats via activation of α7nAChRs, which was associated with a decrease in glutamate levels, inhibition of synaptic remodeling, and improvement of cholinergic transmission in the hippocampus. Hence, our findings not only suggest that cytisine represents a promising anti-epileptic drug, but provides evidence of α7nAChRs as a novel therapeutic target for TLE.